Parameter analysis in Probabilistic Cellular Automaton model for fire spread simulation in Sete Cidades National Park - Brasiel, Heitor Castro; Lima, Danielli Araújo (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2024: Anais do XV Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2024)
This study investigates forest fire dynamics in Sete Cidades National Park, a Cerrado Biome area, using cellular automaton models. We examine how varying wind speeds and vegetation scenarios affect fire spread, analyzing their impact on burned area expansion. By simulating fire spread across varied landscapes, we analyze the impact of wind velocities w = {5, 20} on the expansion of burned areas over successive iterations, roughly doubling the burned area (b) rate. Heterogeneous vegetation varies in fire susceptibility, with certain scenarios, like Rupestrian Cerrado and Clean Camps, suffering more damage. Our simulations can aid wildfire management, emphasizing the importance of considering environmental factors to effectively mitigate fire risks in the Cerrado biome.